2020
DOI: 10.1007/s00134-020-05949-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ebola-related critical illness

Abstract: To explore contemporary clincial case management of patients with Ebola virus disease. Methods: A narrative review from a clinical perspective of clinical features, diagnostic tests, treatments and outcomes of patients with Ebola virus disease. Results: Substantial advances have been made in the care of patients with Ebola virus disease (EVD), precipitated by the unprecedented extent of the 2014-2016 outbreak. There has been improved point-of-care diagnostics, improved characterization of the clinical course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 42 publications
(97 reference statements)
0
41
0
2
Order By: Relevance
“…According to The New England Journal of Medicine [11], the first case in the United States (reported in Washington State) was treated with an intravenous administration of Remdesivir which mitigated symptoms, and did not cause any side-effects [11]. However, prior clinical trials in Ebola reported side effects such as liver inflammation, nausea, sweating, shivering, and low blood pressure [69]. Remdesivir is currently in clinical trial evaluation for the treatment of COVID-19 in various countries including France (NCT04365725), USA (NCT04431453), Canada (NCT04330690), Egypt (NCT04345419) (Table 1).…”
Section: Potential Treatment Strategiesmentioning
confidence: 99%
“…According to The New England Journal of Medicine [11], the first case in the United States (reported in Washington State) was treated with an intravenous administration of Remdesivir which mitigated symptoms, and did not cause any side-effects [11]. However, prior clinical trials in Ebola reported side effects such as liver inflammation, nausea, sweating, shivering, and low blood pressure [69]. Remdesivir is currently in clinical trial evaluation for the treatment of COVID-19 in various countries including France (NCT04365725), USA (NCT04431453), Canada (NCT04330690), Egypt (NCT04345419) (Table 1).…”
Section: Potential Treatment Strategiesmentioning
confidence: 99%
“…Supportive care includes oral rehydration that contains electrolytes [69] preventing complications of shock and fluid resuscitation in Ebola infected people [24,70]. A number of anti-Ebola therapeutics such as anti-viral drugs, monoclonal antibodies, anti-inflammatory agents, convalescent plasma etc were proposed and evaluated during Ebola Virus Outbreak to contain and reduce the risk of the virus [24,71]. Inmazeb, also called REGN-EB3, combination of three monoclonal antibodies and Ebanga (Mab114) -single monoclonal antibody were the only two drugs approved for Ebola treatment by the US Food and Drug Administration (FDA) in the late 2020 [72] which were previously used in a randomized control trial during 2018-2020 Ebola outbreak in Democratic Republic of Congo and resulted in high survival rate [68].…”
Section: 4present Containment Strategies Of All Outbreaksmentioning
confidence: 99%
“…Inmazeb, also called REGN-EB3, combination of three monoclonal antibodies and Ebanga (Mab114) -single monoclonal antibody were the only two drugs approved for Ebola treatment by the US Food and Drug Administration (FDA) in the late 2020 [72] which were previously used in a randomized control trial during 2018-2020 Ebola outbreak in Democratic Republic of Congo and resulted in high survival rate [68]. Another therapeutic called ZMapp, cocktail of three monoclonal antibodies also proved to be superior to standard care for Ebola Virus Disease treatment [71].…”
Section: 4present Containment Strategies Of All Outbreaksmentioning
confidence: 99%
“…Erforderlich sind bei diesen Patienten vor allem das Monitoring der Vitalparameter, Labortestungen, intravenöse Flüssigkeitsgabe, die Applikation von vasoaktiven Medikamenten und Sauerstoff, Beatmung und Nierenersatztherapie (Abb. 2 ; [ 16 ]). Die Sterblichkeit in Westafrika betrug zwischen 39 und 70 %.…”
Section: Virale Hämorrhagische Fieber – Lokale Katastrophen Mit Interunclassified
“…Dass die Überlebensrate durch moderne Intensivmedizin deutlich verbessert wird, zeigen die Erfahrungen bei Patienten, die während der Epidemie in andere Industriestaaten evakuiert wurden. So betrug die Sterblichkeit bei in Europa und in den USA behandelten Patienten nur 18,5 % [ 16 , 17 ]. Der hierfür notwendige klinische und materielle Aufwand ist in den Endemieländern nicht zu leisten.…”
Section: Virale Hämorrhagische Fieber – Lokale Katastrophen Mit Interunclassified